Assessment of Psychiatric Symptoms During Lockdown due to the COVID‑19 Pandemic in a Child and Adolescent Psychiatry Clinical Population - Vieira da Costa , Carolina (2021)
The COVID‑19 pandemic implied the lockdown of the paediatric population at home, conditioning changes in academic and leisure activities and relations with peers and family. Children and young people with mental illness have specific vulnerabilities, which can be affected in a particular way. This study aims to evaluate the evolution of psychiatric symptoms ‑ in the domains of mood, anxiety and behavioral changes ‑ in a child and adolescent psychiatry (CAP) population during the lockdown due to COVID‑19. Data were collected through a telephone interview with the main caregiver of children/young people (for psychiatric symptoms and qualitative variables) and online filling of the Strengths and Difficulties Questionnaire (SDQ). Data were subsequently analyzed statistically in SPSS. The final sample consists of a total of 502 patients. There was a global increase in screen hours, along with changes in hours of physical activity and sleep. Additionally, there was an increase in symptoms of sadness, irritability, anxiety and behavior. It was demonstrated that these symptomatic variations were statistically correlated with the caregiver’s perception of the variation in the quality of the relationship during lockdown. With specific vulnerabilities, this population can be affected differently depending on the diagnosis and on the social and family context. Longitudinal studies are justified, as well as analyzes that identify risk and protective factors.